Long waves in Argentine economic development - Federico Foders; Hans H. Glismann (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1985)
Argentine economic development from 1864 to 1983 can be roughly devided into a period of economic progress (1864 - 1930) and into one of economic decline (1930 - 1983). Of the many issues that could potentially explain such an unprecedented development of a basically resource-rich country, this paper deals with distributional conflicts, inflation, exogenous shocks and political instability. The analysis shows that redistributive incomes policies in favour of labour and government accomodated by a very loose monetary policy seem to lie at the heart of an institutionalised distributional conflict over a stagnant national income. To the extent that political instability can be associated with the underlying distributional conflict the political cycle hypothesis adds some explanatory power to the above. With the only exception of World War I, which seems to have triggered inward-oriented industrialisation policies, exogenous shocks do not seem to have been of major importance for Argentine economic performance; at best such shocks should have reinforced the negative impact of incomes and monetary policies.
Keywords: 330